I have a problem with following exercise (it comes from Geoffrey G. Grimmett, David R. Stirzaker, Probability and Random Processes, Oxford University Press 2001, page 161, ex. 3a):

Let $X$ have the Poisson distribution with parameter $Y$ where $Y$ has the Poisson distribution with parameter $\mu$. Show that $$G_{X+Y}(s) = e^{\mu(s e^{s-1} - 1)}$$

So $G_Y(s) = e^{\mu(s-1)}$ Now I want to compute $G_X$ (is this approach correct?) $$G_X(s) = \sum_{x=0}^{\infty} s^x P(X=x) = \sum_{x=0}\sum_{y=0} s^x \frac{e^{-y} y^x}{x!} \frac{e^{-\mu} \mu^y}{y!}$$ $$G_X(s) = e^{-\mu} \sum_{x=0} \frac{s^x}{x!} \sum_{y=0} \frac{y^x e^{-y}\mu^y}{y!}$$

And I don't know how to cope with this summation.

Secondly, are these variables independent? I.e. can I use then following formula? $$G_{X+Y}(s) = G_X(s) G_Y(s)$$

Thanks for your help.


1 Answer 1

  1. $X$ and $Y$ are not independent, since $X$ has been defined using $Y$.

  2. The easiest way to compute $G_{X+Y}(s)={\Bbb E}s^{X+Y}$ is to first condition on $Y$. So, first, $$ {\Bbb E}[s^{X+Y}\mid Y]=s^Y{\Bbb E}[s^X\mid Y]. \qquad (*) $$ Since $X$ is Poisson with parameter $Y$, conditioned on $Y$, the pgf of $X$ is $e^{Y(s-1)}$. Plugging this into (*) gives $$ {\Bbb E}[s^{X+Y}\mid Y]=s^Y e^{Y(s-1)}. \qquad (**) $$ The only remaining step is to take the expectation of (**). Since the right-hand side of (**) is of the form $\alpha^Y$, this can be done by plugging $\alpha$ into the pgf for $Y$. This gives the desired result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.